PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF BERBASIS INKUIRI TERBIMBING PADA MATERI REAKSI OKSIDASI REDUKSI KELAS X SMA/MA - Hidayanti, Melly (rc-institut, 2019)
The reduction oxidation reaction material is abstract. abstract material learning can be done by displaying three levels of chemical representation, namely macroscopic, sub-microscopic and symbolic. One of the learning media that can display three levels of chemical refresher is powerpoint. In powerpoint media a learning model can be applied that can guide students actively in finding and finding concepts. Guided inquiry is a learning model that fits the demands of the 2013 curriculum and is able to guide students actively in finding concepts. The type of research used to obtain products is research and development (R & D) with 4-D models. The instrument of this research was in the form of a validity test and practicality questionnaire. The media developed was validated by 5 validators, namely 3 chemistry lecturers and 2 chemistry teachers. The practicality test questionnaire was filled by 2 chemistry teachers and 25 students of grade X science at SMAN 1 Sungai Aur. the results of the validity and practicality tests were analyzed using the Cohen Kappa formula. From the results of the validity test data analysis, the average kappa moment was 0.87 with a very high validity category. From the results of the practicality test data analysis on the teacher, the average kappa moment was 0.97 and the students were 0.94 with a very high practicality category. Based on the results of the study, it can be concluded that the guided inquiry-based interactive powerpoint learning media on the developed oxidation reduction material is valid and practical.